Controlling quantum resonances in photonic crystals and thin films with electromagnetically induced transparency - Ooi, Chong Heng Raymond; Kam, C.H. (American Physical Society, 2010)
Quantum coherence or phaseonium medium with electromagnetic-induced transparency (EIT) may have been widely explored, but the incorporation of boundaries into finite structures like thin films and photonic crystals introduce additional resonant features. A narrow transmission peak exists in resonant medium due to multiple reflections and interference. The corresponding analytical formulas for absorptive and EIT media are derived. A double dip feature is found only for transverse magnetic polarized light, due to longitudinal electric field component in a Fabry-Perot thin film. We study these resonant features in a finite superlattice and discuss potential applications of the features. For phaseonium medium with laser-driven gain, transmission and reflection peaks beyond unity appear between the two EIT resonances. Realizations using solid-state materials such as doped crystals and quantum dots with potential applications are discussed.